Quantification and Determination of Stability of Tylvalosin in Pig Plasma by Ultra-High Liquid Chromatography with Ultraviolet Detection - Verónica Hernandis; Elisa Escudero; Juan Sebastián Galecio; Pedro Marín (Animals, 2022)
Tylvalosin (TV) is a macrolide antibiotic that is used for treating respiratory and enteric bacterial infections in swine and in poultry. In the coming years, the use of this drug will probably be widely studied in different species, but before its use in each veterinary species, macrolide analytical determination in various biological fluids is a pre-requisite step for the rational dose calculation of TV based on specific pharmacokinetic information. Its quantification is essential for detecting and avoiding the appearance of residues in animal products intended for human consumption. Therefore, a robust chromatographic method coupled with an ultraviolet detector was fully validated for the quantification of TV in pig plasma. A mixture (78:22) of (A) 0.3% formic acid in water and (B) acetonitrile was used as the mobile phase. TV and enrofloxacin (internal standard) were eluted at 14.1 and 5.9 min, respectively. Calibration curves ranged from 0.1 to 5 μg/mL. The accuracy and precision parameters for the quality controls were always <13.0%. Recovery ranged from 89.66 to 96.92%. The detection and quantification limits were found to be 0.05 μg/mL and 0.1 μg/mL, respectively. This method could be applied to develop pharmacokinetic studies.